Land Tenure Conflicts After the End of Use Rights for Plantation Legal Entities in Indonesia - Alpi Sahari (Budapest International Research and Critics University, 2021)
Land problems almost occur throughout Indonesia, without exception in Medan, North Sumatra Province. In Medan there is PTPN II land which, due to community needs, the government chose not to extend the HGU (Hak Guna Usaha) for the benefit of the community. The government considers that the people need this land more in order to meet the needs of life and the welfare of the entire community. The method used in this paper is juridical normative by adopting a legal synchronization approach, both vertically and horizontally, on land tenure conflicts after the expiration of the Legal Entity for Plantation Companies in Indonesia. Data obtained through literature search. The results show that the provisions regarding land tenure have been regulated in Law number 5 of 1960 concerning Basic Agrarian Principles or often referred to as UUPA. In article 16 paragraph 1 of Law Number 5 of 1960 UUPA, it is stated that land rights include ownership rights, land use rights, building use rights, usage rights, lease rights, land opening rights, rights to collect forest products, other rights that are not included in the rights mentioned above which will be stipulated by law as well as rights which are temporary as mentioned in Article 53 of Law Number 5 concerning UUPA. The existence of land rights that have been regulated in law often creates confusion and overlaps in the control of the land object. There is still a lack of and low understanding of the law by the majority of the community, are often used by irresponsible individuals with the intention of obtaining benefits in the form of land rights through control of the land. Then the role of the government has not run optimally in protecting the rights of land controlled by the community. The government has not been able to collect data and make complete registrations of land tenure in Indonesia. This is the cause of the frequent occurrence of land tenure conflicts so that the participation of all levels of society as well as the government is urgently needed..